EFEKTIVITAS PRENATAL YOGA TERHADAP KECEMASAN DAN KELUHAN FISIK IBU HAMIL TRIMESTER II - hutari puji astuti; Wahyu Dwi Agussafutri (Institut Kesehatan dan Teknologi Al Insyirah, 2021)
A pregnant woman often experiences many changes, both physical changes and psychological changes. This condition will always cause a feeling of physical discomfort to the pregnant woman, coupled with an image of the delivery process, how the baby is and the condition of the baby after birth. Such images are common in pregnant women who are about to undergo labor. Conditions like that can cause feelings of anxiety in pregnant women, especially in women who are pregnant for the first time (primigravida). The goal of prenatal yoga is to prepare pregnant women physically, mentally and spiritually for childbirth. With careful preparation, the mother will be more confident and gain confidence in going through labor smoothly and comfortably. This study aims to determine the effectiveness of prenatal yoga on anxiety and physical complaints of second trimester pregnant women at PMB Wulan Mardikaningtyas Singopuran Kartasura Sukoharjo. The research method used is this research is a type of quantitative research with the type of pre-experimental research using one group pre and posttest research design, namely research that uses only one group of subjects, measurements are carried out before and after treatment. This research was conducted at PMB Wulan Mardikaningtyas Singopuran Kartasura Sukoharjo by providing a questionnaire about anxiety and physical complaints during pregnancy in the second trimester. Then pregnant women are given physical treatment in the form of prenatal Yoga once a week for one month. Univariate analysis performed the frequency distribution and Wilcoxon test and Mann Whitney test with α = 0.05 and CI95%. The results of this study are that there is a significant relationship between prenatal yoga and the anxiety of trimester II pregnant women as evidenced by a probability value (p) 0.042 <0.05 and there is a significant relationship between prenatal yoga and complaints of pregnant women in trimester II as evidenced by the probability value ( p) 0.015 <0.05.